Strategies of Marketing Mix and Its Role in Increasing of Market Share: Exploring Study for The Opinions of Employees in City Centre Company at Zakho City - Omr, Mohammed A.; Mohammed, Rosh I.; Ali, Nazar M. (Humanities Journal of University of Zakho, 2015)
The Research aimed to determine the relationship between marketing mix strategies and market share in the (City Centre) company which located in Zakho. The Research using descriptive analytical method to test a random sample of (40) of the staff who work as supervisors and executives the involved company. To collect the data, questionnaire has been used to measure the Research dimensions, and to measure impact between the dimensions of the Research, in order to find out the answers of the Research problems and to reach to the Research objectives. The Research used (SPSS) program for analyzing the data.The company works in an environment characterized by abrupt changes which make the company to be a source of a set of restrictions surrounding its work to choose an effective marketing mix strategy. Accordingly, the Research suggests that the company need to give more attention to its pricing policy through adjusting its prices based on the levels of customers income which, in turn, enhance its market share and outperform the competitors.